Assumption of snow temperature near Shirase Glscier from analysis of radio echo sounding data (abstract) - Izumi, Tatsuji; Hoshiyama, Mitsuo; Nishitsuji, Akira; Wada, Makoto; Mae, Shinji; Kusunoki, Kou (1983)
P(論文) departmental bulletin paper